The Effect of Workload and Auditor Experience on the Auditor's Ability to Detect Fraud at Public Accounting Firms - Tolewo, Thesiana Sangiang; Kurniawati, Elisabeth Penti (Journal La Sociale, 2024)
This research aims to examine and analyze the influence of workload and auditor experience on the ability of auditors to detect fraud. The respondents of this study are auditors working at Public Accounting Firms in Semarang City. This research is a quantitative study. The sampling technique used was convenience sampling, with a total sample of 74 respondents. Multiple linear regression is employed for data analysis at a significance level of 5%. Data were collected through the distribution of questionnaires. The results indicate that workload does not have an effect on the auditor's ability to detect fraud, while auditor experience has a positive and significant effect on the auditor's ability to detect fraud.